TARGET 2 and the Eurozone's balance of payments crisis - Vilímovský, Petr (2014)
This thesis aims to analyse the connection between the Eurozone's balance of payments crisis and the TARGET 2 balances. These balances represent mutual clearing relationship of the individual euro area member states to the European Central Bank inside the TARGET 2 system, which serves as a heart of the Eurozone's payment settlements. In fact, the central banks of the core countries hold significant positive balances while the peripheral central banks accumulated substantial negative positions. The TARGET 2 balances appeared mainly as a consequence of the liquidity outflow from the peripheral countries to the core due to the large imbalances in fundamental factors such as the NCA deficits, net foreign debt, public and private debt or competitiveness. The development of the balances was further facilitated via uneven liquidity provisions from the Eurosystem, as the peripheral countries effectively financed their balance of payments disequilibrium by issuing new liquidity that almost immediately moved to the core. The banking systems of the core started to operate in the liquidity excess status as the monetary base increased in 2011 and 2012. Assets with questionable quality collateralized the increasing refinancing operations in the periphery as the collateral requirements were repeatedly lowered. It resulted in an increase in the credit risk of these operations primarily in the periphery countries. This situation, among many others presented in this thesis, raises further questions about the parameters of the future single monetary policy as well as the continuance of the European monetary union.